THE ANALYSIS OF MINIMUM WAGE ON EMPLOYMENT: STUDY IN EAST JAVA - Marcellacornelia, Rosalina (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this research is to analyze the influence of minimum wage towards employment. This study used quantitative panel data as the method. Data used were time-series data from 2009 to 2012. The data collected were secondary data collected from the website of Badan Pusat Statistik (BPS). The analysis method used in this research was regression analysis of linear panel data (pooled data) using Model Fixed Effect as the instrument to process the data using Eviews 7. The result of this research showed that minimum wage gave influence to the employment in East Jawa, while GRDP (Regional Gross Domestik Product) and the total of industry did not give influence to the employment in East java.Keywords : Employment, Minimum Wage, GRDP, Total of Industry